PENGARUH KUALITAS PRODUK, KUALITAS PEMBELIAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK TABUNGAN BERHADIAH LANGSUNG PT. BANK BUKOPIN TBK - Trisyandi, Kurnia Yudha; Mulyowahyudi, Alugoro (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aims to examine and analyze the effect of product quality, service quality and brand image of the decision to purchase savings products directly prizes in PT. Bank Bukopin. This type of research is conducted quantitatively, where researchers used 142 respondents in West Jakarta who bought savings products with prizes directly. Meanwhile, the sampling technique is done by Purposive Sampling. The tool used to analyze the data is with SPSS 21 program. Of the four variables studied, the most dominant service quality is seen to the purchase decision. Therefore, the leadership of Bank Bukopin in West Jakarta should improve the quality of service in this case from the physical evidence side. Due to visible dimensions of physical evidence more dominant to the purchase decision. To meet the quality of service in accordance with the expectations of customers must pay more attention to the location of a good office, comfortable room design, interior, employee uniforms, business cards, billboards and other communication materials so that service quality can be more leverage